2002
DOI: 10.1038/sj.onc.1205835
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressor genes on chromosome 3p involved in the pathogenesis of lung and other cancers

Abstract: Loss of heterozygosity (LOH) involving several chromosome 3p regions accompanied by chromosome 3p deletions are detected in almost 100% of small (SCLCs) and more than 90% of non-small (NSCLCs) cell lung cancers. In addition, these changes appear early in the pathogenesis of lung cancer and are found as clonal lesions in the smoking damaged respiratory epithelium including histologically normal epithelium as well as in epithelium showing histologic changes of preneoplasia. These 3p genetic alterations lead to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
274
1
7

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 349 publications
(291 citation statements)
references
References 145 publications
(165 reference statements)
9
274
1
7
Order By: Relevance
“…28,49 The codon 326 polymorphism may be in linkage disequilibrium with other functional polymorphisms in cancerrelated genes on chromosome 3p. 50 In summary, the hOGG1 codon 326 Ser/Ser genotype was associated with an increase in p53 mutations in tobacco-related NSCLC. However, no difference in the pattern of oxidative damage (G:C-to-T:A transversions) was evident among codon 326 genotypes.…”
Section: Discussionmentioning
confidence: 86%
“…28,49 The codon 326 polymorphism may be in linkage disequilibrium with other functional polymorphisms in cancerrelated genes on chromosome 3p. 50 In summary, the hOGG1 codon 326 Ser/Ser genotype was associated with an increase in p53 mutations in tobacco-related NSCLC. However, no difference in the pattern of oxidative damage (G:C-to-T:A transversions) was evident among codon 326 genotypes.…”
Section: Discussionmentioning
confidence: 86%
“…A stearate-Fus1 peptide inhibits the tyrosine kinase activity of c-Abl Fus1 is a TSG associated with NSCLC (Kondo et al, 2001;Zabarovsky et al, 2002). A C-terminal deletion mutant of FUS1 was isolated from a lung cancer tumor cell line, which encodes the first 80 amino acids of the 110-amino-acid wild-type Fus1 protein (Kondo et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, new approaches in the treatment of NSCLC have arisen from the discovery that the epithelial growth factor receptor (EGFR) is frequently overexpressed and activated in NSCLC (Dowell and Minna, 2005). In lung cancer, loss of sequences within chromosome 3p is frequently seen in both SCLC and NSCLC, providing evidence of tumor suppressor genes (TSGs) in this chromosomal region (Girard et al, 2000;Zabarovsky et al, 2002). The FUS1 gene has been identified in the 3p21.3 critical chromosomal region and is considered a novel TSG (Zabarovsky et al, 2002;Ji et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,5,7,8 Tumor suppressor genes (TSGs) on chromosome 3p play a key role in the pathogenesis of human lung cancer and other cancers. [9][10][11][12][13] FUS1 is one of novel candidate TSGs clustered in a 120-kb homozygous-deletion region in the human chromosome 3p21.3 region. 14,15 We have previously demonstrated that the forced expression of wild-type (wt)-FUS1 significantly inhibited tumor cell growth by induction of apoptosis and alteration of cellcycle kinetics in 3p21.3-deficient NSCLC cells in vitro, and efficiently suppressed tumor growth and metastasis in mouse models of human lung cancer.…”
Section: Introductionmentioning
confidence: 99%